High-throughput sequencing of core STR loci for forensic genetic investigations using the Roche Genome Sequencer FLX platform. (August 2011) - Fordyce, Sarah L.; Ávila-Arcos, Maria C.; Rockenbauer, Eszter; Børsting, Claus; Frank-Hansen, Rune; Petersen, Frederik Torp; Willerslev, Eske; Hansen, Anders J.; Morling, Niels; Gilbert, M. Thomas. P.
The analysis and profiling of short tandem repeat (STR) loci is routinely used in forensic genetics. Current methods to investigate STR loci, including PCR-based standard fragment analyses and capillary electrophoresis, only provide amplicon lengths that are used to estimate the number of STR repeat units. These methods do not allow for the full resolution of STR base composition that sequencing approaches could provide. Here we present an STR profiling method based on the use of the Roche Genome Sequencer (GS) FLX to simultaneously sequence multiple core STR loci. Using this method in combination with a bioinformatic tool designed specifically to analyze sequence lengths and frequencies, we found that GS FLX STR sequence data are comparable to conventional capillary electrophoresis-based STR typing. Furthermore, we found DNA base substitutions and repeat sequence variations that would not have been identified using conventional STR typing